Kinetic analysis of segmentation gene interactions in Drosophila embryos. - Nasiadka, A.; Krause, H.M. (Development, 1999)
A major challenge for developmental biologists in coming years will be to place the vast number of newly identified genes into precisely ordered genetic and molecular pathways. This will require efficient methods to determine which genes interact directly and indirectly. One of the most comprehensive pathways currently under study is the genetic hierarchy that controls Drosophila segmentation. Yet, many of the potential interactions within this pathway remain untested or unverified. Here, we look at one of the best-characterized components of this pathway, the homeodomain-containing transcription factor Fushi tarazu (Ftz), and analyze the response kinetics of known and putative target genes. This is achieved by providing a brief pulse of Ftz expression and measuring the time required for genes to respond. The time required for Ftz to bind and regulate its own enhancer, a well-documented interaction, is used as a standard for other direct interactions. Surprisingly, we find that both positively and negatively regulated target genes respond to Ftz with the same kinetics as autoregulation. The rate-limiting step between successive interactions (<10 minutes) is the time required for regulatory proteins to either enter or be cleared from the nucleus, indicating that protein synthesis and degradation rates are closely matched for all of the proteins studied. The matching of these two processes is likely important for the rapid and synchronous progression from one class of segmentation genes to the next. In total, 11 putative Ftz target genes are analyzed, and the data provide a substantially revised view of Ftz roles and activities within the segmentation hierarchy.